In vitro biocompatibility of a sandblasted, acid-etched HA composite coating on ultrafine-grained titanium. Issue 11 (3rd February 2021) - Chi, Yanxia; An, Sipeng; Xu, Yunpeng; Liu, Mingda; Zhang, Jie
Abstract : A sandblasted, acid-etched hydroxyapatite (SLA-HA) composite coating on ultrafine-grained titanium was synthesized by sandblasting, acid etching and electrophoresis deposition. Abstract : A sandblasted, acid-etching hydroxyapatite (SLA-HA) composite coating on ultrafine-grained titanium was synthesized by the sandblasting, acid etching and electrophoresis deposition. Mouse osteoblasts (MC3T3-E1) were cultured in vitro and inoculated on the SLA-HA composite coating of the ultrafine-grained titanium. Using ultrafine-grained titanium with SLA coating as the control group, the adhesion and proliferation of the osteoblasts were analyzed using the CCK-8 assay. The number and morphology of the cells were observed using a laser confocal microscope. Cells toxicity of the cytotoxicity to osteoblasts was studied by culturing them in an immersion solution of the SLA-HA composite coating. The hemolysis properties of the obtained material were assessed using fresh rabbit blood. Ultrafine-grained titanium with the SLA-HA composite coating was found to have no significant toxicity to osteoblasts, as well as good blood compatibility, playing a positive role in the adhesion of osteoblasts and promoting their proliferation and differentiation.